2020
DOI: 10.3390/jcm9092938
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Ischemic Strokes of Patients with Atrial Fibrillation and Therapy with Anticoagulants

Abstract: Background: Reducing the number of ischemic strokes in patients with atrial fibrillation despite oral anticoagulation remains an important, yet largely unsolved challenge. Therefore, we assessed the etiology of ischemic strokes despite anticoagulation with vitamin K antagonists (VKA) or non-VKA oral anticoagulants (NOACs). Methods: Patients with known atrial fibrillation (AF), treatment with VKA or NOAC, and acute ischemic stroke admitted between 2015 and 2018 (1st half) were identified from the hospital datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Recent data from Purrucker et al suggest that non-adherence to medication, under-dosage of anticoagulants, or their temporary discontinuation frequently precede AF-related stroke despite OAC. 9 This is in line with our findings that suggest that 65.93% of the patients on VKA that experienced an ischemic stroke were not on therapeutic range. Hence, it is of paramount importance to investigate the individual circumstances of a stroke occurring on anticoagulants and to address the multiplicity of underlying factors in subsequent prevention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent data from Purrucker et al suggest that non-adherence to medication, under-dosage of anticoagulants, or their temporary discontinuation frequently precede AF-related stroke despite OAC. 9 This is in line with our findings that suggest that 65.93% of the patients on VKA that experienced an ischemic stroke were not on therapeutic range. Hence, it is of paramount importance to investigate the individual circumstances of a stroke occurring on anticoagulants and to address the multiplicity of underlying factors in subsequent prevention.…”
Section: Discussionsupporting
confidence: 91%
“…Potential causes include inadequate dosing and non‐adherence to medication as well as competing other stroke etiologies, such as small vessel disease or large artery atherosclerosis. Insight into stroke subtype, pattern and location of cerebral infarction and potentially competing non‐cardioembolic stroke mechanisms of these patients is sparse 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent (2014-2019) Swiss cohort study showed that 18% of all AF patients with ischemic stroke had been on prior VKA therapy and 20% on orior DOAC therapy [16••]. Reasons for ischemic stroke despite anticoagulation include competing stroke etiology or mechanisms (e.g., large-artery atherosclerosis, small-vessel disease, active malignancy [17][18][19][20][21], medication error (e.g., non-adherence, inappropriate DOAC dosage, or subtherapeutic INR) as well as cardioembolism despite anticoagulant therapy. However, recent studies found that prior therapeutic anticoagulation with VKA or DOAC was associated with lower stroke severity [16 Intravenous thrombolysis with alteplase is the gold standard in the treatment of acute ischemic stroke with significant improvement in functional outcome [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while the relative risk of hemorrhagic strokes has been halved by using NOACs as compared to warfarin, a vitamin K antagonist (VKA), the rate of ischemic stroke has remained largely unchanged [ 1 ]. Consequently, acute ischemic stroke (AIS) develops frequently despite oral anticoagulation [ 2 , 3 ]. Current evidence about the optimal treatment strategies in patients with AIS under therapy with NOACs is still limited [ 4 ].…”
Section: Introductionmentioning
confidence: 99%